Gestão do trabalho das pessoas com deficiência no campo da saúde pública - Siqueira, Raquel de Amorim (2015)
The presence of people with disabilities - PwD is ever more frequent in public organizations due to the reservation of vacancies for such professionals provided by law. These organizations are not always prepared, either architecturally or by a culture of inclusion, to receive and manage the workforce. In this context, the present study sought to discuss the management practices of people with disabilities in the public sector, from the inclusion approach, using the case of the Instituto Nacional de Câncer José Alencar Gomes da SilvaINCA. For the construction of this study, it was conducted a qualitative survey which included documentary analysis and semi-structured interviews. In order to encompass the views of different groups of people who are involved with the issue in the INCA, three types of professionals were interviewed, namely: servers with disabilities, managers directly linked to these PwD and head of human resources management area. It is possible to see a concern of the institute to fulfill the legal requirement of employment quotas reserved in the establishment plan for PwD, but it was identified empirically have not yet been developed or adapted, institutional management instruments for the effective inclusion of these professionals. It was also found that the adaptation of the INCA to accessibility dimensions - architectural, communicational, methodological, instrumental, programmatic and attitudinal - is still incipient. Formally, there is no element that prevents the participation of PwD in the INCA people management subsystems. However, the necessary tools to autonomy and full participation of these professionals are not always created and institutionalized.